Chronic experimental autoimmune encephalomyelitis is an excellent model to study neuroaxonal degeneration in multiple sclerosis - Voskuhl, Rhonda R.; MacKenzie-Graham, Allan (Frontiers in Molecular Neuroscience, 2022)
Animal models of multiple sclerosis (MS), specifically experimental autoimmune encephalomyelitis (EAE), have been used extensively to develop anti-inflammatory treatments. However, the similarity between MS and one particular EAE model does not end at inflammation. MS and chronic EAE induced in C57BL/6 mice using myelin oligodendrocyte glycoprotein (MOG) peptide 35-55 share many neuropathologies. Beyond both having white matter lesions in spinal cord, both also have widespread neuropathology in the cerebral cortex, hippocampus, thalamus, striatum, cerebellum, and retina/optic nerve. In this review, we compare neuropathologies in each of these structures in MS with chronic EAE in C57BL/6 mice, and find evidence that this EAE model is well suited to study neuroaxonal degeneration in MS.